2020
DOI: 10.3390/ani10020327
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Milk Yield and Quality Traits in a Large Population of Water Buffaloes

Abstract: The buffalo milk industry has economic and social relevance in Italy, as linked to the manufacture of traditional dairy products. To provide an overview of the current status of buffaloes’ performances on a large scale, almost 1 million milk test-day records from 72,294 buffaloes were available to investigate milk yield, energy corrected milk, fat, protein, and lactose content, and somatic cell score (SCS). Phenotypic correlations between milk traits were calculated and analysis of variance was carried out thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
11
20
0
1
Order By: Relevance
“…However, a comprehensive comparison with the literature was not possible, TABLE 5 | Significance of linear (P L ) and quadratic (P Q ) regression coefficient of maximum temperature-humidity index (MTHI) and least squares means of bulk milk traits for the fixed effect of MTHI with significance (P) of the effect (three classes). Table 2) were overall in agreement with those reported in literature for Mediterranean water buffalo and based on individual milk samples (7,13). Moreover, some correlations, like those of THI with milk FC, PC, and LC, were in line with the trend observed for the LSM in the three classes of THI (Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, a comprehensive comparison with the literature was not possible, TABLE 5 | Significance of linear (P L ) and quadratic (P Q ) regression coefficient of maximum temperature-humidity index (MTHI) and least squares means of bulk milk traits for the fixed effect of MTHI with significance (P) of the effect (three classes). Table 2) were overall in agreement with those reported in literature for Mediterranean water buffalo and based on individual milk samples (7,13). Moreover, some correlations, like those of THI with milk FC, PC, and LC, were in line with the trend observed for the LSM in the three classes of THI (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Descriptive statistics observed in this study for FC, PC, LC, SCS, and coagulation traits mirrored those reported in studies based on bulk milk data collected on 36 Italian buffalo herds (11) and on 1,414,449 individual buffalo milk test-day records (7). As expected, the variability of the bulk milk traits was lower compared with individual samples (7).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In buffalo routine management, the set-up of milking devices is a critical point and the characteristics of milking vacuum and milking pulsations are strictly connected with milk flow observations ( 18 , 20 , 22 ). It is well-established that udder health influences milk composition and milk flow parameters in dairy species, including buffalo ( 23 , 24 ). In buffalo, as in other dairy species, the milk somatic cell count (SCC) is the most adopted indicator for udder health and mastitis ( 12 , 23 25 ).…”
Section: Introductionmentioning
confidence: 99%